Pemanfaatan Software GeoGebra dalam Materi Geometri Analitik untuk Siswa Kelas XI: Survey terhadap Respon Siswa - Desty Septianawati; Zulkarnain; Ressy Rustanuarsi (Universitas Veteran Bangun Nusantara, 2025)
Analytic geometry is a branch of mathematics that requires a deep understanding of concepts, yet it often poses significant challenges for high school students. This study aims to describe students' responses to the use of GeoGebra software in learning mathematics, specifically in the context of analytic geometry. Employing a descriptive method with a quantitative approach, the research was conducted with a population of 150 eleventh-grade students from SMA Negeri 10 Pontianak. A sample of 75 students was selected using random sampling techniques. Data were collected through questionnaires and analyzed using descriptive statistics. The findings revealed that students responded very positively to the use of GeoGebra software in the learning process of analytic geometry. All participants reported that the software enhanced their understanding of analytic geometry concepts, particularly in terms of visualization. Furthermore, nearly all students expressed their intention to continue using GeoGebra and recommended it to others, citing its user-friendly interface and its ability to make learning more engaging and interactive. This study highlights the potential of GeoGebra as an effective tool for improving the teaching and learning of analytic geometry.